An Improved Measure of Ethical Leadership. (February 2013) - Yukl, Gary; Mahsud, Rubina; Hassan, Shahidul; Prussia, Gregory E.
The appropriate way to define and measure ethical leadership has been a source of conceptual confusion in the leadership literature. Different measures have been developed, but they all have limitations. Some questionnaires are missing key indicators of ethical leadership, or they include behaviors that do not seem directly relevant. In this study, the authors assess the validity of a new questionnaire for measuring essential aspects of ethical leadership independently of other types of leader behavior. The research also examines how ethical leadership is related to leader–member exchange and work unit performance. Although the primary purpose of these analyses is to assess criterion-related validity for the new questionnaire, the results help answer important questions about the benefits of ethical leadership. The authors found that ethical leadership makes a small but significant contribution to the explanation of leader–member exchange and managerial effectiveness.